Young people’s lived sexual and reproductive health citizenship: participation and power of youth in Malawi - Jannah Wigle; Stewart Paul; Anne Emanuelle Birn; Brenda Gladstone; Monica Kalolo; Paula Braitstein; Lisa Forman; Lumbani Banda (Global Public Health)
This qualitative, focused critical ethnographic study explores how young people’s ‘lived SRH citizenship’ and their active roles realising their sexual and reproductive health (SRH) and rights, shape their agency and participation in decision-making in Malawi. Informed by postcolonial feminist and difference-centred citizenship theories, our findings reveal that age-based power differentials, systems of gerontocracy and a culture of adultism impede bona fide youth involvement in SRH policymaking, making young citizens’ participation more of an illusion than reality. Although democratisation and decentralisation aim to promote youth engagement, SRH policy spaces/processes lack institutionalised processes for integrating youth and remain dominated by donors and government. Collective efforts to build young citizens’ capacity and to support their engagement are essential for realising their active and meaningful participation in SRH decision-making. Recognising youth as equal members of society is vital to expose systemic gerontocracy/adultism, and democratise power to youth in Malawi, and beyond.